Chronic intermittent intravenous immunoglobulin in heart transplant recipients with elevated donor‐specific antibody levels. Issue 2 (9th November 2021) - Yopes, Margot; Fanek, Tala; Fuselier, Byron; Gaine, Maureen; Jackson, Ruslana; Mabasa, Angelo; Kim, Andrea; Jennings, Douglas L; Clerkin, Kevin; Yuzefpolskaya, Melana; Habal, Marlena; Latif, Farhana; et al.
Abstract: Donor‐specific antibodies (DSA) are associated with antibody‐mediated rejection (AMR) and poor patient survival. In heart transplant, the efficacy of intermittent intravenous immunoglobulin (IVIg) in reducing de novo DSA levels and treating AMR has not been characterized. We retrospectively studied a cohort of 19 patients receiving intermittent IVIg for elevated DSA and examined changes in DSA levels and graft function. Intermittent IVIg infusions were generally safe and well tolerated. Overall, 23 of 62 total DSA (37%) were undetectable after treatment, 21 DSA (34%) had MFI decrease by more than 25%, and 18 (29%) had MFI decrease by less than 25% or increase. The average change in MFI was ‐51% ± 71% ( P  < .001). Despite reductions in DSA, among the six patients (32%) with biopsy‐confirmed AMR, left ventricular ejection fraction (LVEF) decreased in five (83%) and cardiac index (CI) decreased in three (50%). Conversely, LVEF increased in 91% and CI increased in 70% of biopsy‐negative patients. All six AMR patients were readmitted during treatment, four for confirmed or suspected rejection. IVIg infusions may stabilize the allograft in patients with elevated DSA and negative biopsies, but once AMR has developed does not appear to improve allograft function despite decreasing DSA levels.